2006
DOI: 10.1007/s11802-006-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

226Ra and 228Ra in the seawater of the western Yellow Sea

Abstract: Radium isotopes 226Ra and 228Ra in seawater of the western Yellow Sea were measured by using the Mn-fiber adsorption -HPGe y spectrum method. The distribution features of the two isotopes have been studied. The activities of 226Ra and 22SRa are 2.72-5.57 Bqm 3 and 7.51-34.3 Bqm 3, respectively. The activities of 226Ra and 228Ra from surface to bottom for each depth profile station are comparable within the experimental error, but the mean activities decrease with distance from the shore. From the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Since sulphate and nitrate in the aerosol particles were positively correlated with the microbes of the fine particle range (1.1–2.1 μm), this might be because of nitrogen and sulphur as nutrients. 55 In our study, NH 3 shows a positive correlation with total microbe count, which may result in NH 3 acting as the nutrient for microbial growth. O 3 is toxic to the microbes, and studies found that the concentration of microbes decreases with the increase in O 3 concentration.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Since sulphate and nitrate in the aerosol particles were positively correlated with the microbes of the fine particle range (1.1–2.1 μm), this might be because of nitrogen and sulphur as nutrients. 55 In our study, NH 3 shows a positive correlation with total microbe count, which may result in NH 3 acting as the nutrient for microbial growth. O 3 is toxic to the microbes, and studies found that the concentration of microbes decreases with the increase in O 3 concentration.…”
Section: Resultssupporting
confidence: 52%
“…Moreover, some microbes were very complex, and some of them became new dominant species while changing the atmospheric conditions. 55,56 Thus, the change in the community structure and accumulation of the higher concentrations of the particles may be the result of higher concentrations of the bioaerosols in the foggy days of winter.…”
Section: Association Of the Bioaerosols With Particulate Matter Durin...mentioning
confidence: 99%
“…The 228 Ra activities in the SYS during this cruise ranged from 32 to 127 dpm 100 L 21 (supporting information Table S1). Using literature in the same area, we also summarized 228 Ra data from Nozaki et al [1991], Kim et al [2005], Men et al [2006], and Zhang [2007], and all the data fall into the high level among the world's ocean surfaces [Cochran, 1992], which may be due to the relative shallow depth of the SYS that 228 Ra may diffuse from bottom sediments, and as a semienclosed margin sea, that SGD-derived 228 Ra may come from land. Surface 228 Ra activity showed considerable spatial variations in the study area.…”
Section: Ra In the Water Columnmentioning
confidence: 99%